2012
DOI: 10.1016/j.jcmg.2012.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Adrenergic Augmentation of Diastolic Intra-LV Pressure Difference in Patients With Diastolic Dysfunction

Abstract: In patients with preserved EF, DD is associated with a reduced adrenergic augmentation of the IVPD from the mid-LV to the LV apex, reflecting less apical suction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 38 publications
1
47
1
Order By: Relevance
“…The current study enrolled subjects with an earlier stage of HFpEF, where filling pressures were closer to normal at rest and physical examination evidence of congestion was largely absent. Despite the absence of right-sided structural remodeling, RV systolic and diastolic function were significantly impaired in the HFpEF group, differences that became more evident in the setting of β-stimulation, similar to prior studies evaluating LV-systemic arterial reserve with adrenergic stimulation [9][10][11][12][13] or exercise stress. 36,37 In HFpEF subjects, tricuspid annular s′ increased with dobutamine in relation to afterload reduction from dobutamine rather than an increase in contractility, which would manifest by an upward shift in the s′ versus PA pressure relationship.…”
Section: Rv Dysfunction and Rv-pa Coupling In Hfpefsupporting
confidence: 76%
“…The current study enrolled subjects with an earlier stage of HFpEF, where filling pressures were closer to normal at rest and physical examination evidence of congestion was largely absent. Despite the absence of right-sided structural remodeling, RV systolic and diastolic function were significantly impaired in the HFpEF group, differences that became more evident in the setting of β-stimulation, similar to prior studies evaluating LV-systemic arterial reserve with adrenergic stimulation [9][10][11][12][13] or exercise stress. 36,37 In HFpEF subjects, tricuspid annular s′ increased with dobutamine in relation to afterload reduction from dobutamine rather than an increase in contractility, which would manifest by an upward shift in the s′ versus PA pressure relationship.…”
Section: Rv Dysfunction and Rv-pa Coupling In Hfpefsupporting
confidence: 76%
“…Loss of this response impacts the capacity to enhance early filling as the diastolic interval shortens during exercise or adrenergic challenge. In patients with diastolic dysfunction, augmentation of the atrialapical LV pressure gradient during dobutamine infusion was reduced, with greatest impairment in patients with mild dysfunction (23). The prolongation of IVRT c during dobutamine suggests that SHRs recapitulate this aspect of clinical diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 94%
“…The healthy left ventricle functions as a 'vacuum cleaner' that prevents LA hypertension by enhancing suction in response to increases in venous return, as with exercise. 51,[66][67][68][69][70][71] This role is achieved through the generation of intraventricular pressure gradients that are determined by the speed of relaxation, the extent and velocity of mitral annular longitudinal motion, the LV 'untwisting' that occurs during early diastole, and the end-systolic volume (ESV) achieved in the preceding contraction cycle (reduced ESV below the equilibrium volume increases recoil to enhance filling, like a compressed spring). 51,72,73 Studies have shown that each of these components is impaired in patients with HFpEF, particularly during the stress of exercise, such that the left ventricle can fill only at the expense of left atrial hypertension.…”
Section: Pathophysiological Components Of Hfpefmentioning
confidence: 99%
“…51,72,73 Studies have shown that each of these components is impaired in patients with HFpEF, particularly during the stress of exercise, such that the left ventricle can fill only at the expense of left atrial hypertension. 17,24,33,70,71 In other words, although the healthy left ventricle effectively pulls in blood during early diastole, [66][67][68] in patients with HFpEF, filling is reliant on high LA pressure to push blood into the chamber (Figure 1). 28,29,33,68,69 Ventricular passive diastolic stiffness is also an important determinant of the increase in LV filling pressures in HFpEF.…”
Section: Pathophysiological Components Of Hfpefmentioning
confidence: 99%